A NARRATIVE INQUIRY INTO LIVED EXPERIENCES OF INDONESIAN EFL TEACHERS EMPLOYING CLASS ASSESSMENTS - Muhana, Arkan Farras; Zain, Dodi Siraj Muamar (Program Studi Pendidikan Bahasa Inggris Fakultas ilmu Budaya, 2025)
This research retells stories of Indonesian English as a Foreign Language (EFL) teachers regarding their experience employing different types of assessments in their classrooms. The research aims to understand how educators in Indonesia view assessment practices in EFL learning environments. A qualitative approach using narrative inquiry research type was used along with semi-structured interviews and non-participant observation as data collection methods. Four EFL teachers from two vocational high schools in Central Java, Indonesia, were recruited to describe the types of learning assessments used and the perceived benefits and challenges of various assessment methods. The findings reveal that EFL teachers face various challenges in designing assessments, including ensuring student honesty and aligning assessments with learning objectives. The research also highlights the importance of formative and summative assessments, as well as the integration of Assessment for Learning (AfL), Assessment of Learning (AoL), and Assessment as Learning (AaL) in the assessment process. The results of this research provide valuable insights for policymakers, curriculum developers, and educational institutions to improve assessment policies and practices, better aligning them with the goals of EFL education in Indonesia.